Effect of thermal cycles on optical properties of epoxy resin reinforced with graphene and carbon nanotubes - Parkhomenko, Irina N.; Vlasukova, Liudmila A.; Parfimovich, Ivan D.; Kamyshan, Alexander S.; Zhukova, Maria N. (Journal of the Belarusian State University. Physics, 2025)
The effect of thermal cycling under conditions equivalent to 16 h in near-earth orbit on the optical absorption of pristine epoxy resin and epoxy-based polymers with the addition of graphene nanoplatelets and multi-walled carbon nanotubes has been studied. The coefficient of absorption of solar radiation (αs) and the emissivity (ε) in the thermal IR range of the synthesised polymers were determined. It was shown that the addition of 1 wt. % of carbon filler leads to an increase in αs from 0.88 to 0.94–0.95 and ε from 0.93 to 0.95–0.96. It was found that thermal cycling results in an increase in αs of the sample with graphene nanoplatelets by 0.5 %. In the case of the sample with carbon nanotubes αs decreased by 0.4 %. The coefficient of absorption of solar radiation of the unmodified epoxy resin decreased by about 2 % after thermal cycling. The emissivity increased by ∆ε = 0.006 (0.6 %) for unmodified epoxy resin and by ∆ε = 0.002 (0.2 %) for the samples with carbon fillers after thermal cycling. Based on the optical and Fourier transform IR spectroscopy data, the physical processes occurring in composites during thermal cycling combined with UV radiation are discussed.
Keywords: thermal cycles; epoxy resin; graphene; carbon nanotubes; absorption of solar radiation